Foundation in Science Studies - Biological Field Trip Report: Introduction to Documentation of Nepenthes Species in Bako National Park, Sarawak - Mohamad Fhaizal, Mohamad Bukhori; Rohaiza, Daud; Christharina, Saurin Gintoron; Roberta Chaya Tawie, Tingga; Raziman, Imam Ghazali (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
In order to accomplish the learning objectives of ecology, biodiversity and environment course, in situ activities remain the finest key to complement by conducting real fieldwork experiments. The specific objectives of the fieldwork are to ensure sustainable learning, adopting best practice in scientific documentation, and implementing holistic and integrated learning approach in the course. Therefore, related field topic was given to the students and resulted with the following attributes. Four different species of pitcher plants were identified and classified throughout the study. The recent biology educational trip to Bako National Park had documented various well-known species of Nepenthes. Information on Nepenthes species present in the parks is useful for educational and research purposes, developing a conservation plan and management and also helps in promoting ecotourism. The trip was conducted to introduce a comprehensive learning experience to the students in biodiversity-related discipline.